The species of the genus Schendylurus Silvestri 1907 of Argentina, Brazil and Paraguay (Chilopoda Geophilomorpha Schendylidae) - Pereira, Luis Alberto (1996)
Three new species of Schendylurus Silvestri 1907 are described, i.e. S. coscaroni n. sp. from State of São Paulo, Brazil; S. demartini n. sp. from Province of Misiones, Argentina and S. placcii n. sp. from Province of Formosa, Argentina. Seven further species of the same genus are redescribed, viz., S. bakeri Chamberlin 1914 (after the holotype); S. demelloi Verhoeff 1938 (after the lectotype and paralectotype); S. fieldi (Chamberlin 1944) (after the holotype); S. iguapensis Verhoeff 1938 (after the holotype); S. olivaceus Crabill 1972 (after the holotype); S. parahybae (Chamberlin 1914) (after the holotype); S. paulista (Brölemann 1904) (after the holotype). Additional data on S. demangei Pereira 1981 are given (after the holotype). New material is cited of S. mesopotamicus Pereira 1981 and S. pampeanus (Pereira & Coscarón 1976). The new combination S. parahybae (Chamberlin 1914) is presented, this species originally described under Adenoschendyla Brölemann & Ribaut 1911, being transferred from Pectiniunguis Bollmann 1890. A key is provided for the identification of the species of Schendylurus from Argentina, Brazil and Paraguay.